Luckiest Girl Alive: A Novel - Knoll, Jessica; Maby, Madeleine ([New York] : Simon & Schuster Audio, 2015)
A New Yorker named Ani FaNelli, who seems to have at all: a dream job, a handsome fiance and an apartment in trendy Tribeca. But, Ani is actually clinging desperately to a veneer of perfection that is about to come undone because a documentary film threatens to reveal a violent, sordid incident from her past.
Keywords: Young women -- Fiction; Women journalists -- Fiction; Life change events -- Fiction; Secrecy -- Fiction; New York (N.Y.) -- Fiction; Suspense fiction; Audiobooks